ANALISIS PERSONAL BRANDING RUBEN ONSU MELALUI INSTAGRAM - aletta bimantoro (JIKE: Jurnal Ilmu Komunikasi Efek, 2020)
With the modern era, social media can now be used as building one's self-image through personal branding. Personal Branding can be built through social media Instagram. Building personal branding can be done by demonstrating our abilities, talents, or establishing a business in any field, one of which is food. Various methods are used to establish personal branding, such as the example conducted by Ruben Onsu on the Instagram account of GeprekBensu, when Ruben Onsu conducted a campaign about the originality of its products. The formulation of the problem is What is the form of Ruben Onsu's personal branding in the GeprekBensu Instagram account? The purpose of this research is to find out personal branding formed by Ruben Onsu through GeprekBensu's Instagram social media. The research method used is qualitative, the research model is descriptive by collecting data through GeprekBensu Instagram account documentation. The data analysis method is divided into 3 namely reduction, data presentation, and conclusion testing. The results of the discussion from this study are that Ruben Onsu builds personal branding with various supporting features such as his followers, uploads his Instagram photos, effects on his photos, and the use of sentences or symbols in the photos are then described into 8 the concept of formation of personal branding namely specialization, leadership, personality, differences, looks, unity, determination, and good name.